2011
DOI: 10.3109/17435390.2011.562328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary gold nanoparticles in zebrafish at very low contamination pressure: The role of size, concentration and exposure time

Abstract: The impact of a daily ration of food containing gold nanoparticles (AuNPs) of two sizes (12 and 50 nm) was investigated in the zebrafish Danio rerio at very low doses (from 36-106 ng gold/fish/day). AuNP exposure resulted in various dysfunctions at the sub cellular scale, and AuNP concentration in food, AuNP size and exposure duration modulated the observed adverse effects. Indeed, we showed alteration of genome composition using a RAPD-PCR genotoxicity test as the number of hybridization sites of the RAPD pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 55 publications
2
60
1
Order By: Relevance
“…Even though limited information exists about their fate and persistence in the aquatic environment (Peijnenburg et al 2015), evidence is building that indicates NPs are taken up by aquatic organisms at different trophic levels (Hoolbrook et al 2008;Cleveland et al 2012;Hou et al 2013;Khan et al 2015). Trophic transfer has been proposed as an important process for NP uptake in fish (Cedervall et al 2012;Geffroy et al 2012;Ladhar et al 2014;Skjolding et al 2014;Batel et al 2015;Mattsson et al 2015), and furthermore it could be suggested that the internal transport, localisation and subsequent toxicity of NPs may differ for organisms through aqueous and dietary exposure. In general, there is a lack of information on the extent of NP uptake at the organism level, and recent concern has been raised regarding the relationship between the uptake route and internal localisation of NPs both in vivo and in vitro (Bondarenko et al 2013;Fabrega et al 2011;Ma et al 2013;Menard et al 2011;Scown et al 2010;Tourinho et al 2012;Xin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though limited information exists about their fate and persistence in the aquatic environment (Peijnenburg et al 2015), evidence is building that indicates NPs are taken up by aquatic organisms at different trophic levels (Hoolbrook et al 2008;Cleveland et al 2012;Hou et al 2013;Khan et al 2015). Trophic transfer has been proposed as an important process for NP uptake in fish (Cedervall et al 2012;Geffroy et al 2012;Ladhar et al 2014;Skjolding et al 2014;Batel et al 2015;Mattsson et al 2015), and furthermore it could be suggested that the internal transport, localisation and subsequent toxicity of NPs may differ for organisms through aqueous and dietary exposure. In general, there is a lack of information on the extent of NP uptake at the organism level, and recent concern has been raised regarding the relationship between the uptake route and internal localisation of NPs both in vivo and in vitro (Bondarenko et al 2013;Fabrega et al 2011;Ma et al 2013;Menard et al 2011;Scown et al 2010;Tourinho et al 2012;Xin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression may provide a molecular level of understanding of how nanomaterials interact with the organism and how NPs with different properties may differentially impact an organism . For example, exposing zebrafish to negatively charged AuNPs induces genes associated with mitochondrial dysfunction in brain and muscle tissues (Geffroy et al, 2012). Exposing golden clams to AuNPs caused not only oxidative stress but an induction of metallothionein (Renault et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…44 In zebrafish Danio rerio exposed to low doses of 12 nm and 50 nm Au NPs, size and exposure length modulated the genotoxicity and the expression of genes involved in DNA repair, apoptosis, and oxidative stress. 45 Flow cytometry and real-time PCR analysis of apoptotic genes and ATP depletion measurements suggested that 17 nm Au NPs induced cell damage through extrinsic and intrinsic apoptotic pathways in human lung adenocarcinoma A549 cells. 46 Au NPs (12 nm) were internalized by the endolysosomal pathway in Balb/3T3 fibroblasts after 10 days of exposure, and although they were not a severe cytotoxicant, Au NPs induced DNA damage.…”
mentioning
confidence: 97%